MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA KONKRET DAN VISUAL PADA SISWA KELAS VII E SMP NEGERI 2 PEMANGKAT TAHUN PELAJARAN 2016/2017 - Syahrial, Syahrial (Jurnal Kajian Pembelajaran dan Keilmuan, 2018)
AbstractThis study aims to improve the activity and learning outcomes of students' mathematics using concrete and visual media. The subjects of this study were students of class VII E SMP Negeri 2 Pemangkat Sambas regency. Instruments used in the form of observation sheets to observe student activities during the learning and test the learning outcomes. In this study, observations were made of concrete-looking activities, including: visual activities, oral activities, motor activities, and mental activities. This category of research is Classroom Action Research (PTK) conducted in 2 cycles, in which each cycle consisting of planning, implementation, observation, and reflection. The result of the research shows that the increase of student activity from cycle I to cycle II is good visual activity from 68,75% in cycle I to 81,25% in cycle II, oral activity from 66,67% in cycle I to 70,83% at cycle II, motor activity from 68,75% in cycle I to 81,25% in cycle II, mental activity from 62,5% in cycle I to 66,67% in cycle II. With the average percentage of activity (PK) of 66.25% in the first cycle increased to 73.75% in cycle II. Thus, the students’ activities reach the indicator of the success of the research because it has reached ≥ 70%. The average of the first cycle test results of 63.16 increased to 67.54 in cycle II. While the percentage of students who reached KKM value 72 in cycle I and second cycle increased by 34.37% in cycle I 56.25% in cycle II, increased by 21.88%. The conclusion of this study is using concrete and visual media can increase activities and learning outcome of mathematics student of class VII E SMP Negeri 2 Pemangkat Sambas regency.. Keywords: Student Activities and Learning outcome, concrete and visual media